How does a company overcome a declining performance through strategic internationalization decisions? : the long-term growth strategies of SUMOL+COMPAL - Sarmento, André Vargas de Oliveira de Moraes (2020)
The following dissertation has its main research focus on SUMOL+COMPAL’s business performance between two-time frames. The first one between 2008 and 2012 characterized by declining performances immediately after the merger between Sumolis and Compal in 2008, a period of recession in the Portuguese national territory, marked by a very strong macroeconomic crisis. The second time frame, from 2013 until now, one of performance recovery, is analysed, presenting the strategies which made such positive turnaround possible. Through strategic internationalization decisions allied to continuous and disruptive innovation, SUMOL+COMPAL was not only able to survive one of the harshest recessions hitting its main market (Portugal), but to come out of it a stronger, more dynamic and international company. By linking theoretical concepts to a real case of positive performance recovery by a declining company, this dissertation will present itself as a value-added material for any strategic, international and innovation area, enabling teachers and students to incur in constructive discussions and debates.